Detection of apoptosis in pemphigus vulgaris by TUNEL technique - Juan Carlos Cuevas-Gonzalez; Maria Elisa Vega-Memíje; Francisco Javier García-Vázquez; Marco António Aguilar-Urbano (Anais Brasileiros de Dermatologia, 2016)
Abstract: Background: Pemphigus is part of a group of blistering diseases that affect the skin and mucous membranes. Based on its autoimmune origin, autoantibodies develop in pemphigus that are directed toward cell surface components of keratinocytes. However, some data cannot be explained, such as the lack of a relationship between autoantibody levels and the severity of clinical manifestations, treatment resistance, the presence of inflammatory infiltrates and the potential occurrence of apoptosis as determinants of vesicle formation. Objective: To examine the presence of apoptosis in pemphigus vulgaris by TUNEL technique. Methods: In this cross-sectional study, we selected 15 paraffin-embedded tissues from subjects who were diagnosed with pemphigus vulgaris by hematoxylin and eosin staining. The samples were subjected to TUNEL assay and examined under an Olympus BX61 fluorescence microscope. Positivity was categorized dichotomously, and the statistical analysis was performed using the X2 test. Results: Positivity was observed in basal layer cells in 14 (93.3%) cases. In 13 (86.7%) of the positive cases, we noted espinosum and granular layers that formed the blister roof, and in 12 cases (80%), positive acantholytic cells were observed. Conclusions: TUNEL positivity was observed in pemphigus vulgaris, implicating apoptosis in the pathophysiology of this condition, which can help guide the development of apoptotic blockers as therapeutics.